Google Classroom-based Online Learning Study Outcomes on Reproductive Concept in Science Classes - Rosalia Dwi Putri (Department of Biology Education, Faculty of Teacher Training and Education, Universitas Muhammadiyah, 2021)
Background: This research shows the improvement of student learning outcomes with Google Classroom-based learning on the concept of human reproductive systems in science classes. Methods: The research method used is the pre-experimental method one-group pretest-posttest design. Samples were taken in non-probability sampling with purposive sampling, which is a science class of 38 students. The treatment given in this study is learning done online using google classroom application, all activities in google classroom on the concept of the human reproductive system. Results: The results of the analysis showed with t calculate (-15.39) greater than t table (-2.04). Based on data analysis and testing, it can be interpreted that there is an increase in student learning outcomes with google classroom-based online learning. The increase is seen from the N-gain value (0.57), which interprets learning outcomes in medium theories. Conclusions: Effectivity learning activities need to be presented by teachers in the face of pandemic situations, although they cannot be done for luring. Google Classroom based online learning can package distance learning more effectively, which has an impact on improving student learning outcomes.